Living at the Speed of Mobile: How Users Evaluate Social Media News Posts on Smartphones. (October 2022) - Keib, Kate; Wojdynski, Bartosz W.; Espina, Camila; Malson, Jennifer; Jefferson, Brittany; Lee, Yen-I
A growing body of research suggests that differences between smartphones and desktop computers influence information processing outcomes. A within-subjects ( N  = 64) smartphone eye-tracking experiment replicates a 2018 desktop-based study of users' visual attention to and engagement with social media news posts. The results show that users spend less time viewing social media news posts on smartphones than desktop, and report lower levels of pleasure and arousal in response to the posts. However, the study found no significant difference between devices in intent to click to read the story and intent to share the post. The findings are discussed with regard to implications for the role of device and attention in communication theory, as well as practical implications for news organizations and other social media content producers.